Effect of temperature on RNA silencing of a negative-stranded RNA plant virus: Citrus psorosis virus - Velázquez, K. (2010)
Citrus psorosis virus (CPsV), genus Ophiovirus, causes a bark scaling disease of citrus. CPsV virions are kinked filaments with three negative-stranded RNA molecules (vRNA) and a 48 kDa coat protein. The effect of temperature on symptom expression, virus accumulation and RNA silencing was examined in sweet orange seedlings (Citrus sinensis) graft-inoculated with three different CPsV isolates and grown in a glasshouse at 26/18°C or 32/26°C (day/night). Most plants kept in the cooler glasshouse showed a shock reaction in the first flush with shoot necrosis, and then moderate to intense chlorotic flecking and spotting in young leaves, whereas plants incubated at 32/26°C did not exhibit shoot necrosis, and young leaf symptoms were milder. Virus titre estimated by ELISA and by northern and dot blot hybridization paralleled symptom intensity, with significantly higher virus accumulation in plants incubated at 26/18°C. The amount of CPsV-derived small RNAs (CPsV-sRNAs) slightly increased at 32/26°C, with the ratio of CPsV-sRNA/vRNA being higher at 32/26°C than at 26/18°C. These results suggest that (i) CPsV infection induces RNA silencing in citrus plants, (ii) symptom intensity is associated with virus accumulation, and (iii) temperature increase enhances the RNA silencing response of citrus plants and decreases virus accumulation.